The use of Digital Resources by pre-service English teachers from a B. A in Bilingualism during Emergency Remote Teaching provoked by the COVID-19 (2022)
This paper gives an account of the digital resources used by pre-service teachers when conducting distance English classes during the Emergency Remote Teaching, caused by the COVID-19 pandemic. This project is a documentary monograph that follows a mixed research approach to analyze lesson plans, journals, reflective papers, and samples of designed material. This work followed the next steps: selection and delimitation of the topic, collection of information, data organization, data analysis, organization of the monograph, writing of the monograph and presentation of the final work. The results of this document shows a classification of the digital resources used, considering their type and frequency. Furthermore, this work presents their instructional and didactic usefulness, as well as the limitations and conditions under which they were used. This monograph aims at contributing further investigations on the ducational disruption in the regional context caused by COVID-19, as well as to highlighting the uses of these resources to enhance teaching practices in online environments.